Peran Orang Tua Dalam Meningkatkan Kemampuan Membaca Al-Qur'an Melalui Metode Talaqqi Pada Anak (Studi Kasus di Rumah Belajar Qur'an Cibabat Cimahi Utara) - Tuti Hernawati (Jurnal Sultra Elementary School, 2026)
This study examines the role of parents in improving children’s Qur’an reading skills through the talaqqi method at Rumah Belajar Qur’an Cibabat, North Cimahi. The research focuses on the importance of family involvement in supporting Qur’an learning in nonformal Islamic education. This study employed a qualitative approach with a narrative study design to explore parents’ experiences and involvement in assisting children’s Qur’an learning. Data were collected through in-depth interviews, observations, and documentation involving teachers and parents selected purposively. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings reveal that parents play significant roles as motivators, facilitators, and learning companions in supporting the implementation of the talaqqi method. Children who received consistent parental guidance and habituation at home demonstrated better fluency, tajwid understanding, and learning discipline in reading the Qur’an. The study also found that collaboration between parents and teachers strengthens the continuity of Qur’an learning beyond the classroom environment. This research contributes to the development of family-based Qur’an learning in nonformal Islamic education by emphasizing the integration of the talaqqi method and parental involvement in improving children’s Qur’an reading skills. The findings imply the importance of strengthening communication and collaboration between families and Qur’anic learning institutions to support sustainable Qur’an education for children.